Total phenolic content and antioxidant activities of corchorus capsularis and stevia rebaudiana extracts - A. R., Hazirah; S., Siti Sarah; A., Syakinah; J., Siti Atika; B., Zainal; M. A., Abdah (2017)
The purposes of this study were to determine total phenolic content (TPC) and antioxidant activities of C.capsularis and S.rebaudiana. Methodology: C.capsularis was extracted successively with methanol and chloroform methanol separately while S.rebaudiana was extracted using methanol and chloroform solvent. The plant extracts were used to conduct various antioxidant assays. TPC assay using Folin-Ciocalteu method was used to assess the presence of phenolic compounds in each sample. The extracts samples were also subjected to assess their potential antioxidant activities through DPPH, ABTS and FRAP assay. The present study showed that both methanol extract of C.capsularis and S.rebaudiana had highest TPC, followed by chloroform extract of S.rebaudiana and chloroform methanol extract of C.capsularis. Next, the DPPH radical scavenging assay was found to be higher in the methanol extract of S.rebaudiana at the concentration of 154.67μg/ml. The cation radical scavenging activity, measured by ABTS assay was shown that methanol extract of S.rebaudiana (278μg/ml) had the lowest EC50 as compared to the other samples. Interestingly, among the various samples, the methanol extract of S.rebaudiana demonstrated a very significant antioxidant activity in FRAP assay (p<0.05). The results of the present study showed that all the extract samples contain significantly high phenolic compounds with superior antioxidant activity as evidence by scavenging of free radical including DPPH and ABTS. In conclusion, it is conceivable that the C.capsularis and S.rebaudiana have shown potential as sources of natural antioxidants.